Impact on food security and rural development of reallocating water from agriculture - Rosegrant, Mark W.; Ringler, Claudia (International Food Policy Research Institute, 1999)
The competition for limited water resources between agriculture and more highly valued domestic and industrial water uses is rapidly increasing and will likely require the transfer of water out of agriculture. This paper reviews and synthesizes the available evidence of the effects of water transfers from agricultural to urban and industrial areas on local and regional rural economies; and analyzes the potential impacts of a large reallocation on global food supply and demand. It concludes with a discussion on the potential for water policy reform and demand management to minimize adverse impacts when water is reallocated from agriculture. It is argued that comprehensive reforms are required to mitigate the potentially adverse impacts of water transfers for local communities and to sustain crop yield and output growth to meet rising food demands at the global level. Key policy reforms include the establishment of secure water rights to users; the decentralization and privatization of water management functions to appropriate levels; the use of incentives including pricing reform, especially in urban contexts, and markets in tradable property rights; and the introduction of appropriate water-saving technologies.